PENGARUH LATIHAN CONTROLLED SPEED POLYGON TERHADAP DAYA TAHAN PADA TIM FUTSAL PUTRI DABORIBO - Yofi Agusni Putri; Slamet '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : this research conducted to find out there is Influence Of Controlled Speed Polygon Exercise Toward Resistance In Female Futsal Team Daboribo so that when doing the competition the atheletes always experiencing fatigue. The kinds of the research was experimental, with the population Daboribo futsal players. The data in this research was the whole population consist of 12 person. Instrument has been done in the research was Bleep test, which aims to measure the resistance ability. After that, the data processed using statistic, to test the normality with liliefors test in the fase of significant 0,05α. Hypothesis proposed was there was Influence Of Controlled Speed Polygon Exercise Toward Resistance In Female Futsal Team Daboribo. Based on the analysis Ttest resulting Tcount 1,836 and Ttab 1,769 it means Tcount > Ttab. And based on the data statistic analysis, the exercise was influential. Even though, there was Influence of Controlled Speed Polygon Toward Resistance in Female Futsal Team Daboribo.Keyword : controlled speed polygon exercise, endurance